2009
DOI: 10.1590/s1413-78522009000500008
|View full text |Cite
|
Sign up to set email alerts
|

Efeito de informação sensorial adicional na propriocepção e equilíbrio de indivíduos com lesão do LCA

Abstract: with the use of additional sensory information (p>0.05). Conclusion: ACL lesion causes damage in the proprioception and postural control system. However, these effects are minimized with the use of additional sensory information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0
13

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 15 publications
0
10
0
13
Order By: Relevance
“…They concluded that addition of sensory information by infrapatellar bandage use improved mobility of older people who usually fall. Studies that investigated changes in postural balance with use of additional sensory information by infrapatellar bandage were carried out on young people with Patellofemoral Pain Syndrome or anterior cruciate ligament injury, and they concluded that the addition of sensory information improved balance 13,26 . Another study evaluated infrapatellar bandage use on people with knee osteoarthritis and concluded that additional sensory information improved biomechanical parameters during task of overcoming obstacles 27 .…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that addition of sensory information by infrapatellar bandage use improved mobility of older people who usually fall. Studies that investigated changes in postural balance with use of additional sensory information by infrapatellar bandage were carried out on young people with Patellofemoral Pain Syndrome or anterior cruciate ligament injury, and they concluded that the addition of sensory information improved balance 13,26 . Another study evaluated infrapatellar bandage use on people with knee osteoarthritis and concluded that additional sensory information improved biomechanical parameters during task of overcoming obstacles 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Uma possível explicação pode ser pelo fato destes participantes não apresentarem déficit proprioceptivo, fato este comprovado ao comparar os valores encontrados neste estudo com os resultados de estudos anteriores 7,13 .…”
Section: Discussionunclassified
“…Isto porque as lesões musculoesqueléticas, como por exemplo, as lesões ligamentares do joelho têm sido associadas a mudanças neuromusculares, como diminuição da propriocepção, diminuição da força muscular e alterações no controle postural [5][6][7][8][9] , principalmente em situações de manutenção do equilíbrio em apoio monopodal sobre o membro lesionado 5,6,8 .…”
Section: Pesquisa Originalunclassified
See 1 more Smart Citation
“…efeito pode aumentar o risco de lesões secundárias[142][143][144] . As alterações proprioceptivas podem ser investigadas através de testes que envolvem a percepção da posição articular[145][146][147][148][149] ou através da avaliação do controle postural 149-151 . O controle postural é determinado por medidas que quantificam a oscilação do corpo em um determinado intervalo de tempo.…”
unclassified